Fertilizer bags at Agricultural Engineering Laboratory (1953)
General view of the Air Control Room at the U.S. Department of Agriculture's Agricultural Engineering Laboratory showing three bags of fertilizer in storage under three bags of sand.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Fertilizer industry--Equipment and supplies; United States. Department of Agriculture